2022
DOI: 10.3389/fnbeh.2022.805124
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Rodent Model for Repetitive Subconcussive Head Impact Exposure in Contact Sport Athletes

Abstract: Repetitive subconcussive head impact exposure has been associated with clinical and MRI changes in some non-concussed contact sport athletes over the course of a season. However, analysis of human tolerance for repeated head impacts is complicated by concussion and head impact exposure history, genetics, and other personal factors. Therefore, the objective of the current study was to develop a rodent model for repetitive subconcussive head impact exposure that can be used to understand injury mechanisms and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“… 4 , 20 , 21 Preclinical studies highlighted neuroinflammatory responses, 52 as well as dose-dependent microgliosis and axonal damage that were correlated to the level of HIE. 55 Chronic studies identified higher later-life t-tau concentrations in former professional football athletes that had sustained higher estimated levels of HIE. 2 These studies have formed the foundation of our understanding of how repetitive subconcussive HIE influences concussion and concussion-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 , 20 , 21 Preclinical studies highlighted neuroinflammatory responses, 52 as well as dose-dependent microgliosis and axonal damage that were correlated to the level of HIE. 55 Chronic studies identified higher later-life t-tau concentrations in former professional football athletes that had sustained higher estimated levels of HIE. 2 These studies have formed the foundation of our understanding of how repetitive subconcussive HIE influences concussion and concussion-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 42 , 58 Recent preclinical modeling also identified significant dose-dependent behavioral changes in rats receiving repeated low-level head accelerations scaled from human contact sport HIE 52 or repeated ‘mild’ exposures. 8 , 47 , 52 , 55 From a mechanistic standpoint, imaging studies identified changes in brain white matter integrity that were positively correlated to levels of HIE. 4 , 20 , 21 Preclinical studies highlighted neuroinflammatory responses, 52 as well as dose-dependent microgliosis and axonal damage that were correlated to the level of HIE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Stemper and colleagues developed a preliminary preclinical model incorporating head rotational acceleration. Their data suggests the ability to scale human subconcussive injury characteristics down to a rodent model with greater accuracy in order to assess the behavioral and physical consequences [ 119 ]. Further research in understanding the mechanism and thresholds of subconcussive injury specific to humans is necessary and ongoing, particularly in regard to frequency of injury exposures and resulting long-term symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the line of thought that each injurious impact an individual sustains may cause physiological and structural changes to the brain, leading to reduced tolerance and increased risk of further injury. Recent preclinical studies have supported this assertion by demonstrating dose-dependent behavioral and pathological changes associated with repeated subconcussive head accelerations [13].…”
Section: Introductionmentioning
confidence: 93%